CP-061 Long-term cost-effectiveness analysis of infliximab, etanercept and adalimumab in rheumatoid arthritis patients in real-life clinical practice. (24th March 2015) - Cardenas, M; Font, P; De La Fuente-Ruiz, S; Viguera-Guerra, I; Casado, M; Castro-Villegas, M; Calvo-Gutierrez, J; Collantes-Estevez, E
Abstract : Background: Anti-tumour necrosis factor-α agents are very effective in the management of rheumatoid arthritis (RA) patients, but superiority among them has not been established. Also, long-term pharmacoeconomic studies examining the cost-effectiveness of biological agents in real-life clinical practice are scarce. Purpose: To assess the efficiency, in terms of cost, of achieving clinical remission (CR), of infliximab, etanercept and adalimumab in a real clinical setting after two years of treatment. Material and methods: All patients diagnosed with RA in a tertiary referral hospital referred through an interdisciplinary consensus protocol who started treatment with infliximab, etanercept or adalimumab between January 2007 and December 2012 were included. Data examined included demographic and clinical variables and use of health-care resources. Effectiveness was measured as the proportion of patients achieving CR after two years of treatment (DAS28 value <2, 6). Costs were assessed from the hospital perspective including the Spanish official drug acquisition costs and costs for diagnostic tests and different medical services, obtained from the Hospital's financial management database. Cost-effectiveness was calculated dividing total health direct costs by percentage of patients achieving clinical remission. Results: 130 patients were included (55 on infliximab, 44 on etanercept and 31 on adalimumab). 45.20% of patients on adalimumab achieved clinical remission after two years, versus 29.1% on infliximab (p = 0.133) and 22.7% on etanercept (p = 0.04), with no significant differences between etanercept and adalimumab (p = 0.475). Mean total health direct costs at two years were €29, 857.67, €25, 328.60 and €23, 309.09 for adalimumab, infliximab and etanercept respectively. The mean costs (IC95%) of achieving CR after two years with adalimumab, infliximab and etanercept were €66, 057 (48, 038–84, 076), €87, 040 (78, 496–95, 584) and €102, 683 (94, 559–110, 807) respectively. Adalimumab was more efficient than etanercept (p < 0.001) and infliximab (p = 0.026), without statistically significant differences between etanercept and infliximab (p = 0.086). Conclusion: Adalimumab was shown to be the most efficient treatment in achieving clinical remission in real-life clinical practice in our hospital. References and/or Acknowledgements: No conflict of interest.